Filling the position of regional head executive task in the regional government system in Indonesia - Win Yuli Wardani,; Nunuk Nuswardani,; Slamet Suhartono, (Technium Social Sciences Journal, 2021)
This type of research is normative juridical research. Based on the results of the research above, it can be concluded that between the appointment of the regional head of the regional head acting acting official and the appointment of the regional head in filling the vacant position of the regional head as follows: (1) If a vacancy occurs because the regional head has entered the At the end of the term of office, the Minister of Home Affairs appoints “Acting” through a Decree of the Minister of Home Affairs and is inaugurated by the Minister of Home Affairs.